The Local Dialect of Brest in Croatian Istria Through the Prism of Slovenian Dialectology - Jakop, Tjaša (Slavia Centralis, 2024)
Brest (Italian: Olmeto) is an Istrian settlement in the far west of Croatia ‒ on the edge of the Karst plateau, not far from the Croatian-Slovenian border. This paper presents and describes the local dialect of Brest, which according to the traditional Croatian dialect classification belongs to north-eastern Buzet or Upper Miren Chakavian dialect, but in phonetic terms (especially with long, i.e. stressed vowels) has many features of the Šavrini subdialect of the Istrian dialect in Slovenia, bordering it in the north. The dialect material for this article was collected in Brest (data-point SLA T413) via to the questionnaire for the Slovenian Linguistic Atlas (SLA) and was compared with the nearest village Rakitovec on the Slovenian side of the border. The phonetics of this border dialect and the words typical of it are further described in this paper.
Keywords: language contact, Buzet dialect, Istrian dialect, Šavrini subdialect, dialect phonetics and dialect lexicon